2008
DOI: 10.1162/edfp.2008.3.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled School Closings and Student Performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 8 publications
6
103
2
5
Order By: Relevance
“…The general pattern in these studies is that the students who have better sleep habits do in fact receive higher grades, but these papers generally only measure simple correlations. 8 More broadly, research on school starting times is related to recent research by economists on the structure of the school day (Eren and Millimet 2007) and the amount of time spent in school (Eren and Millimet 2007;Krashinsky 2006;Marcotte 2007;Marcotte and Hemelt 2008;Hansen 2008;Pischke 2007). Even more broadly, economists studying time use have expanded their analysis beyond the simple hours tradeoff between labor and leisure to include sleep (Biddle and Hamermesh 1990;Brochu, Deri Armstrong, and Morin 2009), other activities (Aguiar and Hurst 2007;Guryan, Hearst, and Kearney 2008;Krueger 2007), and timing of activities throughout the day (Hamermesh 1998(Hamermesh , 1999a(Hamermesh , 1999b(Hamermesh , 2002Hamermesh, Myers, and Pocock 2008 The ACT data is student-level data on all students in grades 10-12 in public schools from the 48 districts (73 schools 2010).…”
Section: A Data and Empirical Methodsmentioning
confidence: 99%
“…The general pattern in these studies is that the students who have better sleep habits do in fact receive higher grades, but these papers generally only measure simple correlations. 8 More broadly, research on school starting times is related to recent research by economists on the structure of the school day (Eren and Millimet 2007) and the amount of time spent in school (Eren and Millimet 2007;Krashinsky 2006;Marcotte 2007;Marcotte and Hemelt 2008;Hansen 2008;Pischke 2007). Even more broadly, economists studying time use have expanded their analysis beyond the simple hours tradeoff between labor and leisure to include sleep (Biddle and Hamermesh 1990;Brochu, Deri Armstrong, and Morin 2009), other activities (Aguiar and Hurst 2007;Guryan, Hearst, and Kearney 2008;Krueger 2007), and timing of activities throughout the day (Hamermesh 1998(Hamermesh , 1999a(Hamermesh , 1999b(Hamermesh , 2002Hamermesh, Myers, and Pocock 2008 The ACT data is student-level data on all students in grades 10-12 in public schools from the 48 districts (73 schools 2010).…”
Section: A Data and Empirical Methodsmentioning
confidence: 99%
“…Marcotte and Hemelt (2008) examined the effect of fewer days of class resulting from snow related school closures on test score performance and found that the pass rate for 3rd grade math and reading assessments falls by more than a half percent for each school day lost to an unscheduled closure. Hansen (2011) examined both school closures due to weather in Colorado and Maryland as well as state-mandated changes in test-date administration in Minnesota and found that in both cases more instructional time prior to test administration increases student performance.…”
Section: Length Of the School Yearmentioning
confidence: 99%
“…A first set of studies (Thile,Thomsen, A related literature exploits exogenous variation provided by natural events, i.e., changes in the number of school days missed due to inclement weather (Marcotte, 2007;Marcotte and Hemelt, 2008;Marcotte and Hansen, 2010), finding that more time in school before tests improves student performance on state-wide exams.…”
mentioning
confidence: 99%